Long‐term cropping system and manure effects on soil health parameters and associated soil‐borne pathogens - Mutai, Joyce; Medvecky, Beth; Vanek, Steven J.; Ojiem, John; Bolo, Peter; Kihara, Job; Fonte, Steven J. (Wiley, 2025)
Soil‐borne pathogens reduce the performance of key food crops in sub‐Saharan Africa. Diversified cropping and nutrient management can enhance soil and plant health, limiting pathogen damage. To examine how management and soil health changes influence soil‐borne pathogens, we leveraged an 18‐year field trial in western Kenya, evaluating cropping systems typical of smallholder farms. We considered three cropping systems and two organic matter management strategies: continuous maize monocrop (M–M), Tephrosia in rotation with maize (T–M), maize intercropped with soybean (M–S), application or not of farmyard manure, and retention or removal of crop residues. We assessed soil physical and chemical properties and major soil‐borne pathogens—Fusarium, Pythium, root knot nematodes (RKN), and lesion nematodes. T–M rotation significantly improved permanganate oxidizable C (POXC), particulate organic matter (POM), aggregation, and available P, while reducing pH and bulk density, compared to other systems. M–S did not significantly improve soil health relative to M–M. Manure reduced RKN by 92% but increased Fusarium by 54%. Soil pH and POXC were negatively correlated with Pythium and RKN, while Fusarium correlated positively with POXC, total C, and aggregation. Overall, continuous nutrient mining and minimal organic inputs led to declines in key soil properties (pH, POXC, POM, aggregation, and total C), with implications for pathogen dynamics. Our findings highlight the importance of organic inputs in enhancing soil health and managing pathogens but caution against using Tephrosia in nematode‐infested soils, as it appears to be a suitable host and may not suppress their populations.